Effect of Adding Gold Nanoparticles on the Anti-Candidal Activity and Release Profile of Itraconazole from Hydrogels - Radosław Balwierz; Paweł Biernat; Dawid Bursy; Mariia Shanaida; Katarzyna Kasperkiewicz; Agata Jasińska-Balwierz; Wioletta Ochędzan-Siodłak (Applied Sciences)
Gold nanoparticles have been identified as a promising avenue for the development of drug carriers, particularly in the context of antimicrobial drug delivery, where limited solubility represents a significant challenge. The ability of gold nanoparticles to penetrate biofilms and disrupt fungal cell membranes makes them an effective tool to support antifungal therapy, especially against resistant strains. Gold nanoparticles also demonstrate synergistic effects with chemotherapeutics and can influence the release profile of the active substances. This study aimed to develop a topical hydrogel drug formulation containing itraconazole (ITZ), with the addition of gold nanoparticles, to enhance its therapeutic properties. Due to ITZ’s poor water solubility, three types of the gold nanoparticles (AuNPs) of different sizes were synthesized and subsequently coated with itraconazole. The resulting formulations were incorporated into carbopol gels and their ability to diffuse through semipermeable membranes was assessed. The findings demonstrated that the combination of gold nanoparticles and itraconazole elevated the diffusion coefficient to twice the level observed in gels without nanoparticles. Furthermore, the combined effect of gold nanoparticles and itraconazole against a reference Candida albicans strain was investigated. The combination of gold nanoparticles and itraconazole demonstrated a growth-inhibitory effect on this strain, indicating that this formulation could potentially be employed in the treatment of fungal infections. The study confirms that hydrogels with itraconazole and gold nanoparticles can be obtained, offering enhanced drug diffusion.